Human Placenta-Derived Multipotent Cells (hPDMCs) Modulate Cardiac Injury: From Bench to Small and Large Animal Myocardial Ischemia Studies. Issue 12 (December 2015) - Liu, Yuan-Hung; Peng, Kai-Yen; Chiu, Yu-Wei; Ho, Yi-Lwun; Wang, Yao-Horng; Shun, Chia-Tung; Huang, Shih-Yun; Lin, Yi-Shuan; De Vries, Antoine A. F.; Pijnappels, Daniël A.; Lee, Nan-Ting; Yen, B. Linju; et al.
Cardiovascular disease is the leading cause of death globally, and stem cell therapy remains one of the most promising strategies for regeneration or repair of the damaged heart. We report that human placenta-derived multipotent cells (hPDMCs) can modulate cardiac injury in small and large animal models of myocardial ischemia (MI) and elucidate the mechanisms involved. We found that hPDMCs can undergo in vitro cardiomyogenic differentiation when cocultured with mouse neonatal cardiomyocytes. Moreover, hPDMCs exert strong proangiogenic responses in vitro toward human endothelial cells mediated by secretion of hepatocyte growth factor, growth-regulated oncogene-α, and interleukin-8. To test the in vivo relevance of these results, small and large animal models of acute MI were induced in mice and minipigs, respectively, by permanent left anterior descending (LAD) artery ligation, followed by hPDMC or culture medium-only implantation with follow-up for up to 8 weeks. Transplantation of hPDMCs into mouse heart post-acute MI induction improved left ventricular function, with significantly enhanced vascularity in the cell-treated group. Furthermore, in minipigs post-acute MI induction, hPDMC transplantation significantly improved myocardial contractility compared to the control group ( p =0.016) at 8 weeks postinjury. In addition, tissue analysis confirmed that hPDMC transplantation induced increased vascularity, cardiomyogenic differentiation, and antiapoptotic effects. Our findings offer evidence that hPDMCs can modulate cardiac injury in both small and large animal models, possibly through proangiogenesis, cardiomyogenesis, and suppression of cardiomyocyte apoptosis. Our study offers mechanistic insights and preclinical evidence on using hPDMCs as a therapeutic strategy to treat severe cardiovascular diseases.